2007
DOI: 10.1677/jme-06-0065
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the human immunodeficiency virus type I long terminal repeat by 1α,25-dihydroxyvitamin D3

Abstract: The genetic predisposition of the host and the virus is the most important determinant for prediction of the course of human immunodeficiency virus type I (HIV-1) viral infection and acquired immune deficiency syndrome (AIDS) progression. Transcription from the HIV-1 long terminal repeat (LTR) is a crucial step for viral replication. Here, we describe a stimulatory role of the vitamin D receptor (VDR) on HIV-1 LTR transactivation. Transient transfections reveal that VDR activates the LTR in HeLa, U937, and Cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Vitamin D deficiency is associated with susceptibility to active TB in both the absence and the presence of HIV infection, but the association is stronger (24), suggesting a potential direct causal relationship between vitamin D deficiency and susceptibility to active TB. In HIV-infected people, vitamin D might also indirectly enhance antimycobacterial immunity by slowing progression of HIV disease (25,26), although studies investigating the effect of vitamin D metabolites on HIV replication in vitro report conflicting results (27)(28)(29)(30)(31). It is biologically plausible, therefore, that vitamin D deficiency impairs antimycobacterial responses in HIV-infected adults and that this phenomenon explains the association between vitamin D deficiency and susceptibility to active TB that we report here.…”
Section: Discussionmentioning
confidence: 71%
“…Vitamin D deficiency is associated with susceptibility to active TB in both the absence and the presence of HIV infection, but the association is stronger (24), suggesting a potential direct causal relationship between vitamin D deficiency and susceptibility to active TB. In HIV-infected people, vitamin D might also indirectly enhance antimycobacterial immunity by slowing progression of HIV disease (25,26), although studies investigating the effect of vitamin D metabolites on HIV replication in vitro report conflicting results (27)(28)(29)(30)(31). It is biologically plausible, therefore, that vitamin D deficiency impairs antimycobacterial responses in HIV-infected adults and that this phenomenon explains the association between vitamin D deficiency and susceptibility to active TB that we report here.…”
Section: Discussionmentioning
confidence: 71%
“…Nevado et al used U937 cells as a model for mononuclear cells (a target for HIV) and demonstrated that VDR and its ligand 1,25-D 3 have a role in transactivation of the long terminal repeat sequence of HIV type 1, which is a crucial element in viral replication. 66 The exact nature of this influence has yet to be fully elucidated. HIV entry into monocytes depends on chemokine receptor CCR5, 67 and vitamin D has a dual role in potentially blocking this step in the infectious pathway.…”
Section: Antimicrobial Efficacy Against Different Infective Agentsmentioning
confidence: 99%
“…Another study found no association between a specific polymorphism and protection against HIV infection in a population of injection drug users, but did find a correlation between specific VDR haplotypes (blocks of polymorphisms) [60]. The authors concluded that protective VDR polymorphisms were associated with reduced VDR function, consistent with vitamin D signaling promoting HIV infection, and noted in an in vitro study that the 1,25D-bound VDR could activate the HIV1 long terminal repeat [61]. Given the recent studies linking vitamin D sufficiency to reduced HIV progression and mother-to-child transmission [50,51] further work regarding links between VDR polymorphisms and HIV appears warranted.…”
Section: Vdr Gene Polymorphisms and Infectious Diseasesmentioning
confidence: 97%